1993
DOI: 10.1002/pro.5560020505
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the maximum change in stability of globular proteins upon mutation of a hydrophobic residue to another of smaller size

Abstract: Although the hydrophobic effect is generally considered to be one of the most important forces in stabilizing the folded structure of a globular protein molecule, there is a lack of consensus on the precise magnitude of this effect. The magnitude of the hydrophobic effect is most directly measured by observing the change in stability of a protein molecule when a n internal hydrophobic residue is mutated to another of smaller size. Results of such measurements have, however, been confusing because they vary gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 27 publications
7
52
0
Order By: Relevance
“…The V to A substitution removes two carbon atoms; the calculated DDG bind for V654A mutant disfavors the mutant by 1.52 kcal/mol, resulting in a destabilization of approximately 0.8 kcal/mol per carbon atom upon cavity formation. This estimate is in good agreement with the results of earlier experimental studies (Kellis et al, 1988;Eriksson et al, 1992;Pace et al, 1996;Loladze et al, 2002) and theoretical calculations (Nicholls et al, 1991;Lee, 1993;Lazaridis et al, 1995). Replacing V with A at position 654 further reflects only in a slight alteration of some other imatinib contact points (E640, T670, C673 and F811) and some ATP-binding residues (K623 and E671).…”
Section: Molecular Modelingsupporting
confidence: 91%
“…The V to A substitution removes two carbon atoms; the calculated DDG bind for V654A mutant disfavors the mutant by 1.52 kcal/mol, resulting in a destabilization of approximately 0.8 kcal/mol per carbon atom upon cavity formation. This estimate is in good agreement with the results of earlier experimental studies (Kellis et al, 1988;Eriksson et al, 1992;Pace et al, 1996;Loladze et al, 2002) and theoretical calculations (Nicholls et al, 1991;Lee, 1993;Lazaridis et al, 1995). Replacing V with A at position 654 further reflects only in a slight alteration of some other imatinib contact points (E640, T670, C673 and F811) and some ATP-binding residues (K623 and E671).…”
Section: Molecular Modelingsupporting
confidence: 91%
“…These observations are also consistent with the view of hydrophobic collapse as a dominant force in protein folding [52]. The effect of environment, hydrophobic clustering, and surface hydrophobicity have all been shown to be important factors in conformation, nucleation, protein folding, and protein-ligand interactions [15,19,39,40,48,[51][52][53][54][55][56][57][58][59]. We have directly demonstrated that the environment plays a critical role Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Second, because the free energy change for helix formation for most residues is positive (the average AGO = 0.54 kcal/mol; Table 2) and the helix propensities of all amino acids except Ala, Leu, and Arg oppose folding, these unfavorable interactions must be overcome either by side-chain-side-chain interactions within the helix or by tertiary interactions, in order for helix formation to occur. The individual free energy changes that accompany helix formation for single amino acids (-0.26 kcal/mol for Ala to 1.6 kcal/mol for Gly) are similar in magnitude to intrahelical sidechain-side-chain interactions such as Glu--Lys+ salt bridges (-0.3 to -0.5 kcal/mol; Scholtz et al, 1993), or burial of a methylene group (-1.8 kcal/mol; Lee, 1993) in a tertiary interaction. Thus, side-chain-side-chain interactions and helix propensities can make roughly equal and opposite contributions to protein folding.…”
Section: Implications For Protein Foldingmentioning
confidence: 90%